الشباب فى السنة النبوية : دراسة موضوعية - حماد، نافذ حسين عثمان; الغرباوى، وليد (الجامعة الإسلامية بغزة - عمادة البحث العلمي والدراسات العليا, 2011)
يدرس البحث فئة الشباب في ضوء السنة النبوية المشرفة، من حيث أهمية الشباب للمجتمع، واهتمام السنة بتربيتهم، والهدي النبوي في معالجة مسألة الشهوة عندهم، وكيف كان الاعتماد عليهم في جيل الصحابة، وتحميلهم بعض المسئوليات.\ ويشتمل على مدخل يجلي مرحلة ما قبل الشباب، والمتعلق برعاية السنة للأسرة، من اختيار للزوج، واهتمام بالطفل عند ولادته، وفي مراحله الأولى. This research studies the category of youth in the light of Sunnah. The introduction sheds the light on wisdoms of starting a family and looking after children in the early stages of their lives. Then it focuses on the importance of the youth for the community and the teachings of Sunnah in bringing up young people. The research highlights the Prophet's guidance in addressing youth issues like teaching them to take responsibilities, directing their energies to the right causes, and handling their sexual desires, and it gives practical examples of how the prophet was relying on the youth in the generation of his companions ‘Sahaba’.
Keywords: الشباب -- الشباب فى الإسلام -- الشباب فى السنة النبوية